Ethical implications of nutritional practices in the digital era: navigating solitude and social connectivity - Lacasella, Giorgia (Progress in Nutrition, 2024)
This study delves into the ethical and social ramifications of nutritional practices amidst the rise of digital consumption patterns, scrutinizing the erosion of traditional commensal relationships and the burgeoning phenomenon of virtual dining experiences. Amidst a cultural backdrop where solitary eating becomes increasingly normative, propelled by the fast-paced, individualistic tendencies of contemporary society, this research critically assesses the shift from physical to virtual spaces of communal eating. It explores how digital platforms, such as metaverse, offer alternative realms of social interaction and identity exploration through food, juxtaposing these against the diminishing practice of shared meals in physical settings. This analysis is situated within a broader discourse on the fragmentation of social bonds and the quest for belonging in the digital age, offering insights into how virtual food experiences both reflect and reshape our understanding of community, solitude, and the ethical dimensions of eating practices. By examining the transition from the communal hearth to the spectacle of online food consumption, the study highlights the complex interplay between food, identity, and social connectivity, proposing a nuanced perspective on the ethical considerations that arise from the digital mediation of nutritional practices.